Optimizing Vendor Management in Construction Companies: A Case Study on Extreme Programming Approach - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
This research aims to optimize vendor management in construction companies through application development using the Extreme Programming (XP) method. The main problems identified were the need for management's lack of efficiency and responsiveness to more change in a dynamic construction environment. The XP method was adopted as a software development approach responsive to change and promotes team collaboration. Data was collected through stakeholder interviews and a literature review to understand user needs and vendor management best practices. The application was developed and tested using predefined criteria. The user acceptance analysis results showed that the application's training session successfully provided an in-depth understanding to 40 users, with 85% of respondents expressing satisfaction with the user interface. Initial usage monitoring showed a high adoption rate, with over 80% of users utilizing key features such as vendor performance monitoring and purchase management. User satisfaction surveys confirmed that 90% of users said the application significantly improved vendor management efficiency.